The Airbus-Boeing dispute: Not for the WTO to solve - Jens van Scherpenberg; Nicolas Hausséguy (Stiftung Wissenschaft und Politik (SWP), 2005)
The Paris Air Show of June 2005, as in previous years, served as the stage for the intense competition between Airbus und Boeing. And given the volume and importance of the market for large civil aircraft, which they share, the two duopolists' increasingly sharp rivalry gets a lot of political attention. The conflict between the United States and the European Union about subsidies for new aircraft, simmering for many years already, was submitted to the World Trade Organization again in May 2005. The WTO, however, is not well-suited to solve this case. It is a purely bilateral dispute in which there is no clear division of the plaintiff's and the defendant's roles between the two sides. Moreover, the WTO dispute-settlement body will be unable to address the main background issue of the conflict - the highly problematic transatlantic defense-industrial relations. Yet the conflict does not necessarily have to lead to a deepening of the trade and security policy rivalry between the European Union and the United States. It could also open up a window of opportunity for both sides to better integrate their mutual defense-procurement markets - thus providing the Atlantic alliance with a much-needed impetus at a critical time. (SWP Comments / SWP)
Keywords: 320